82.9k views
1 vote
Match each function formula with the corresponding transformation of the parent function y = (x - 1)2 1. y = - (x - 1)2 Translated up by 1 unit 2. y = (x - 1)2 + 1 Translated left by 4 units 3. y = (x + 1)2 Translated right by 1 unit 4. y = (x - 2)2 Translated down by 3 units 5. y = (x - 1)2 - 3 Reflected over the x-axis 6. y = (x + 3)2 Reflected over the y-axis

User Shuvalov
by
4.5k points

2 Answers

4 votes

Answer:

the other guys answer

Explanation:

sorry we have been about your car extended warranty this is are last call

User Waliaula Makokha
by
5.5k points
3 votes

Answer:

1.
y = - (x - 1)^(2), Reflected over the x-axis.

2.
y = (x - 1)^(2) +1 , Translated up by 1 unit.

3.
y = (x + 1)^(2) , Reflected over y-axis

4.
y = (x - 2)^(2) ,Translated right by 1 unit.

5.
y = (x - 1)^2 - 3, Translated down by 3 units

6.
y = (x + 3)^2, Translated left by 4 units.

Explanation:

Given that:

Parent function:
y = (x - 1)^(2) Please refer to attached Graph4.

1.
y = - (x - 1)^(2) Sign of y is changed from + to -, so it gets reflected over x axis. Please refer to attached Graph3.

2.
y = (x - 1)^(2) +1: 1 is added to y to translated up (positive y by 1 unit). Please refer to attached Graph3.

3.
y = (x + 1)^(2) , Reflected over y-axis, please refer to attached Graph4.

4.
y = (x - 2)^(2) : 1 is subtracted from x , it gets Translated right by 1 unit. Please refer to attached Graph5.

5.
y = (x - 1)^2 - 3, 3 subtracted from y so it getss translated down by 3 units. Please refer to attached Graph6.

6.
y = (x + 3)^2, 4 added to x, so it gets translated left by 4 units. Please refer to attached Graph5.

Match each function formula with the corresponding transformation of the parent function-example-1
Match each function formula with the corresponding transformation of the parent function-example-2
Match each function formula with the corresponding transformation of the parent function-example-3
Match each function formula with the corresponding transformation of the parent function-example-4
Match each function formula with the corresponding transformation of the parent function-example-5
User Bahaa Hany
by
4.4k points